If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + 6) = 6(x + -3) Reorder the terms: 7(6 + x) = 6(x + -3) (6 * 7 + x * 7) = 6(x + -3) (42 + 7x) = 6(x + -3) Reorder the terms: 42 + 7x = 6(-3 + x) 42 + 7x = (-3 * 6 + x * 6) 42 + 7x = (-18 + 6x) Solving 42 + 7x = -18 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 42 + 7x + -6x = -18 + 6x + -6x Combine like terms: 7x + -6x = 1x 42 + 1x = -18 + 6x + -6x Combine like terms: 6x + -6x = 0 42 + 1x = -18 + 0 42 + 1x = -18 Add '-42' to each side of the equation. 42 + -42 + 1x = -18 + -42 Combine like terms: 42 + -42 = 0 0 + 1x = -18 + -42 1x = -18 + -42 Combine like terms: -18 + -42 = -60 1x = -60 Divide each side by '1'. x = -60 Simplifying x = -60
| 3x-11=10x+12 | | x-(x*0.25)-(x*0.3399)=50000 | | 0=16t^2-300t+2000 | | 21d^2-7d=O | | 6x+4y-2x+5y-5x= | | 12x^3-12x-45=0 | | x+.03x=23.6 | | t(n)=4n-2 | | 7(n-1)=-(3+n) | | k^2+5k-9=0 | | y=-1x^2+29x+12 | | 4r-10= | | 770=3x+77 | | x^2+x=-c | | 5.2+1.7n=1.12 | | 2m+k+3m+2k= | | k+1=k^2+k+c | | 3w+14=50 | | k=-2k^2-k | | 8x+7=5x-21 | | 3(p+4)=24 | | 4y+6y-5=10y-5 | | 5k+40L-35m= | | Sqrt(7x+44)=x | | Ix+7I=2 | | 9-7(5x-8)=63-9x | | 6(x+1)=2(3x+1)+4 | | 11x+5-3x+7= | | x^3+4*x^2+-11*x+30=0 | | 15(a)=225 | | 5x+3=7+5x | | 8(x-3)=-3x-17 |